Social Media and Youth Engagement in a Dynamic World: The Nigerian Perspective - Umuze N. Anthonia; Edih O. University (Budapest International Research and Critics University, 2022)
Effects of globalization are reverberating across human endeavours in modern times and the social media being drivers of globalization are serving as veritable channels for transmitting information and communication from person to person, group to group and nation to nation as well as continent to continent. The unrestrained attitude of youth in the use of social media is rather contagious. It seems to demonstrate the indispensability and high premium placed on social media networks, maybe, due to the rewardable exercise derivable from social networking. Hence, the study seeks to examine social media and youth engagement in a dynamic world: the Nigerian perspective. The main objectives are to demonstrate the indispensable significance of the social media networks in a dynamic world and to secure or devise profitable measures of engaging the youths through the social media. The study is therefore, structured into six perspectives; introduction, general significance of the social media, effects of social media networks, the Nigerian perspective on the use of the social media, engaging the youth through social media, conclusion and recommendations.